0.08x+(0.18)(3)=0.12(x+3)

Simple and best practice solution for 0.08x+(0.18)(3)=0.12(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.08x+(0.18)(3)=0.12(x+3) equation:



0.08x+(0.18)(3)=0.12(x+3)
We move all terms to the left:
0.08x+(0.18)(3)-(0.12(x+3))=0
We add all the numbers together, and all the variables
0.08x-(0.12(x+3))+0.54=0
We calculate terms in parentheses: -(0.12(x+3)), so:
0.12(x+3)
We multiply parentheses
0.12x+0.36
Back to the equation:
-(0.12x+0.36)
We get rid of parentheses
0.08x-0.12x-0.36+0.54=0
We add all the numbers together, and all the variables
-0.04x+0.18=0
We move all terms containing x to the left, all other terms to the right
-0.04x=-0.18
x=-0.18/-0.04
x=4+0.02/0.04

See similar equations:

| 1.36g-4=0.76 | | 12y=-2y+224 | | 2x=20=3x=5 | | 35x^2+3x-2=0 | | 8v=3v+15 | | 2x+20+3x=15 | | 13=p-15+6p | | а+5=-5a+5 | | -18=8(x+6)+4x | | 30=6-3x+9 | | 1/2y+1/7=5/14 | | 3/8.x=450 | | 3(6-x)+12=9 | | 3(6-x)+12=19 | | x/3-4=-12 | | 1/6.x=15 | | -10+s=10+10-4s | | 3-36a=0 | | -10+s=10+10−4s | | x²+3=13 | | x-5.48=0.02 | | 2/5.x=16 | | 7(5y-6)+3=24 | | 2x/3+5/6=13/6  | | 7v=v+48=-2(v+3) | | 8(2x+4)=3(8x-12) | | 5x=(-4x)-(+63) | | 3(y-1)=4y-21 | | 5x=(-4)-(+63) | | v/2+16=42 | | 21=1/3(3-47x | | 8(-4x+2)=2(12-9x)-2× |

Equations solver categories